Sinaes : política de ordenamento para controle e poder do território - Silva, José Adailton Barroso da (2018)
The rise of higher education that started in 90s decade build the Sistema Nacional de Avaliação do Ensino Superior (Sinaes) by the law 10.861, 04/14/2004, which is based on a evaluation of three main components: The institution’s evaluation, course’s evaluation and the student’s performance. This system of evaluation starts to measure the quality and the expansion of new courses and control the offers to job. The analysis developed in this thesis understands that this system is part of the rise of the neoliberal’s project in education, where countries started to rebuild the higher education seeking to attend the Technical Scientific Revolution. This system was installed in various geographic scales, following the model installed in Europe, to bring European universities to the same level of competition as North-American ones, aiming, to measure the quality of education through productivity’s goals. The Thesis’ analysis is driven by the comprehension of education’s inclusion in neoliberal’s logic system. The geographic point of view is fundamental to the debate because it criticize the Sinaes as driver of the reginal development’s speech, and as an instrument of power for territory’s regulation to attend the interest of capital’s hegemonic action, leading to a policy concerned about quality, imposed by syntagmatic’s actors, that involved in the installation, discussion and contradictory crash between the regulation’s need, it controls the territory and legitimate the inequality’s reproduction.